Tissue-specific expression of a Drosophila calcium-activated potassium channel. - Becker, M.N.; Brenner, R.; Atkinson, N.S. (Journal of Neuroscience, 1995)
The Drosophila slowpoke (slo) gene encodes a subunit of a CAK channel homologous to the vertebrate BK channel. We have examined slo expression throughout development. It is expressed in muscle cells, neurons of the CNS and PNS, mushroom bodies, a limited number of cells in embryonic and larval midgut and in epithelial-derived tracheal cells. The promoter has been cloned and shown to direct expression in the same pattern as the endogenous gene in both neural and epithelial-derived cells. During pupariation and embryogenesis, slo is expressed in muscles many hours prior to the appearance of functional channels.